La Memoria Raccontata - Martinelli, Emilia; Belleggia, Silvia (Archeomatica, 2021)
Memory is the ability to preserve and retrieve information along with past experiences. The projects "Garden of Memory" and "Attimi Sospesi" bring to light, from the rubble of the Second World War, the words of the protagonists and the history of Esperia and Cassino. Scientific research, storytelling and digital technologies allow us to piece together, look after and hand down the memory of these communities and lead it to future generations.